Personalized Protein Supplementation Improves Total Protein, Leucine, and Energy Intake in (Pre)Sarcopenic Community-Dwelling Older Adults in the ENHANce RCT - Dedeyne, Lenore; Dupont, Jolan; Verschueren, Sabine; Koppo, Katrien; Tournoy, Jos; Matthys, Christophe; Gielen, Evelien (Frontiers in Nutrition, 2021)
Recommendations concerning protein quantity, source and leucine intake for older adults are difficult to reach by regular dietary intake. This randomized clinical trial assesses in sarcopenic community-dwelling older adults i) the regular (non-supplemented) daily protein and leucine intake; and ii) the effect of personalized protein supplementation (aiming for an evenly distributed total protein intake of 1.5 g·kg-1·d-1 of body mass, accounting for energy intake) on regular and total (dietary and supplemental) intake. A preliminary feasibility study in participants of the ongoing Exercise and Nutrition for Healthy AgeiNg (ENHANce) study was performed with the objective to assess the intake and distribution of regular dietary protein and leucine, protein source and energy intake in (pre)sarcopenic community-dwelling older adults. Moreover, this study aimed to assess if personalized protein supplementation was feasible without negatively affecting regular dietary intake. ENHANce(NCT03649698) is a 5-armed RCT that assesses the effect of anabolic interventions on physical performance in (pre)sarcopenic older adults. In August 2019, n=51 participants were included in ENHANce with complete available data on dietary intake at screening and thus eligible for inclusion in present analysis. Of these, n=35 participants completed the intervention period of ENHANce at the moment of analysis, allowing an exploration of the effect of supplementation on regular dietary intake. The regular dietary protein intake of 51 (pre)sarcopenic adults (73.6 ±6.5 years) was 1.06 ±0.3 g·kg-1·d-1 of body mass. Protein supplementation (n=20) improved total protein intake to 1.55 ±0.3 g·kg-1·d-1 of body mass (P-value <.001) without affecting regular dietary protein (P-value =.176) or energy intake (P-value =.167). Placebo supplementation (n =15) did not affect regular dietary protein intake (P-value =.910) but decreased regular dietary energy intake (P-value =.047). Regular leucine intake was unevenly distributed over the day, but increased by supplementation at breakfast (P-value <.001) and dinner (P-value =.010) to at least 2.46 g leucine·meal-1, without reducing regular dietary leucine intake (P-value =.103). Animal-based protein intake – the main protein source– was not affected by supplementation (P-value =.358). Personalized protein supplementation ensured an adequate quantity and even distribution of protein and leucine over the day, without affecting regular dietary protein or energy intake.